2013
DOI: 10.1039/c3ra42908c
|View full text |Cite
|
Sign up to set email alerts
|

High-performance ultrafiltration membranes based on polyethersulfone–graphene oxide composites

Abstract: Graphene oxide nanosheets are employed as nanofillers to improve hydrophilicity and antifouling performance of a polymer-based membrane, resulting in high performance ultrafiltration membranes with substantially improved flux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 23 publications
3
83
0
1
Order By: Relevance
“…Wang et al 19 Similar results were observed in polyethersulfone (PES)-GO 20 and polysulfone (PS)-GO 26 composite membranes. In addition to the bare GO, functionalized GO nanoparticles as membrane fillers were also reported [27][28][29][30] .…”
Section: Introductionsupporting
confidence: 77%
“…Wang et al 19 Similar results were observed in polyethersulfone (PES)-GO 20 and polysulfone (PS)-GO 26 composite membranes. In addition to the bare GO, functionalized GO nanoparticles as membrane fillers were also reported [27][28][29][30] .…”
Section: Introductionsupporting
confidence: 77%
“…with membranes. 14,25,27,30 This phenomenon was obtained for membranes containing increased amount of GO nanosheets (%). Accordingly, the difference in the adsorbed amounts of BSA among the membranes at pH = 3 may be attributed to the coupling effect of membrane hydrophilicity, membrane charge and membrane morphology.…”
Section: Membrane Permeabilitymentioning
confidence: 75%
“…27,28,36 The detailed procedure for synthesis of GO nanosheets is given in Section S2, Supporting Information. FTIR spectrum for GO nanosheets was recorded as depicted in Fig.…”
Section: Synthesis Of Graphene Oxide Nanosheetsmentioning
confidence: 99%
“…Graphene has notably ing fouling of membrane [34,35]. Jin et al prepared the PES/GO composite ultrafiltration membranes by phase inversion method [35]. Both the hydrophilicity and water flux of the modified PES membranes were improved.…”
Section: Introductionmentioning
confidence: 99%
“…The latest attention toward nanomaterials is paid to graphene, a single 2D carbon sheet with one-atom-layer thickness [18]. Graphene has notably ing fouling of membrane [34,35]. Jin et al prepared the PES/GO composite ultrafiltration membranes by phase inversion method [35].…”
Section: Introductionmentioning
confidence: 99%